Tasting prosody: crossmodal correspondences between voice quality and basic tastes - Motoki, K; Pathak, A; Spence, CJ (Elsevier, 2022)
Voice quality or type of phonation (e.g., a whispery voice) can prime specific sensory associations amongst consumers. In the realm of sensory and consumer science, a wide range of taste-sound correspondences has been documented. A growing body of research on crossmodal correspondences has revealed that people reliably associate sounds with basic taste qualities. Here, we examined the largely unexplored associations between basic tastes and sounds: namely taste-voice quality correspondences. Across three pre-registered studies, participants associated four types of voice qualities (modal, whispery, creaky, and falsetto) with the five basic tastes (sweet, sour, salty, bitter, and umami). Study 1 investigated the relations between voice qualities and taste words. Study 2 attempted to replicate the findings and revealed the underpinning psychological mechanisms in terms of semantic/emotional associations. Study 3 used the descriptions of food products that varied in terms of their taste to expand the applicability of the findings. The results demonstrated that participants reliably associate specific voice qualities with particular tastes. Falsetto voices are matched more strongly with sweetness than other voices. Creaky voices are matched more strongly with bitterness than other voices. Modal voices are matched more strongly with umami than creaky voices. Evaluation/positive valence might partially underlie the associations between sweet/bitter-voice quality correspondences. Taken together, these findings reveal a novel case of sound-taste correspondences and deepen our understanding of how people can associate attributes from different senses.